AN ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING TENSES AT SENIOR HIGH SCHOOL LEVEL - Atrianus Toni (Pedagogic Research-Applied Literacy Journal, 2025)
Mastery of English tenses is a fundamental component in achieving proficiency in English grammar. However, many senior high school students continue to face persistent challenges in understanding and using tenses correctly. This study aims to analyze the types and causes of students’ difficulties in learning English tenses at the senior high school level. Using a descriptive qualitative method, data were collected through classroom observations, student questionnaires, and interviews with English teachers. The findings reveal that the major difficulties encountered by students include confusion in differentiating tense functions, limited vocabulary, lack of practice, and interference from their first language. Moreover, instructional approaches that do not emphasize contextual usage also contribute to students’ misunderstanding. Based on the results, the study suggests that teachers adopt more communicative and contextualized strategies in teaching tenses, such as integrating grammar with speaking and writing activities. This research provides insights into improving grammar instruction to support better learning outcomes in EFL classrooms.